2004
DOI: 10.1002/eqe.395
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the seismic performance of the Bolu Viaduct subjected to near‐fault ground motions

Abstract: SUMMARYThe seismic performance of the Bolu Viaduct in the Duzce, Turkey, earthquake of November 1999 was studied via a non-linear, time-history analysis of a multi-degree of freedom model. The viaduct had a seismic isolation system consisting of yielding-steel energy dissipation units and sliding pot bearings. The Duzce earthquake caused a surface rupture across the viaduct, which resulted in excessive superstructure movement and widespread failure of the seismic isolation system. The e ect of the rupture was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 6 publications
0
44
0
Order By: Relevance
“…A postearthquake investigation at the viaduct site revealed that the fault crosses the viaduct (between Piers P44 and P45) at an angle of about 25 ∘ , and the ground dislocation in the faultparallel direction across the rupture was approximately 1.5 m (59.1 in.). In the analysis by Park et al (2004), two different ground motions, each involving a static slip of 0.75 m (29.55 in.) in opposite directions, were imposed upon the two sides of the ground separated by the surface rupture, resulting in a net ground dislocation of 1.5 m. Results revealed that the static ground displacement had to be accounted for in the dynamic analysis in order to achieve the observed performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A postearthquake investigation at the viaduct site revealed that the fault crosses the viaduct (between Piers P44 and P45) at an angle of about 25 ∘ , and the ground dislocation in the faultparallel direction across the rupture was approximately 1.5 m (59.1 in.). In the analysis by Park et al (2004), two different ground motions, each involving a static slip of 0.75 m (29.55 in.) in opposite directions, were imposed upon the two sides of the ground separated by the surface rupture, resulting in a net ground dislocation of 1.5 m. Results revealed that the static ground displacement had to be accounted for in the dynamic analysis in order to achieve the observed performance.…”
Section: Introductionmentioning
confidence: 99%
“…in opposite directions, were imposed upon the two sides of the ground separated by the surface rupture, resulting in a net ground dislocation of 1.5 m. Results revealed that the static ground displacement had to be accounted for in the dynamic analysis in order to achieve the observed performance. The study asserts that all bridges built close to known faults must have greater displacement capacities than those designed for far-field ground motions [4,5]. Choi et al (2007) studied the effect of fault-rupture [6].…”
Section: Introductionmentioning
confidence: 99%
“…Structural damage caused by the earthquake a) dislodged damper b) Movement in transverse shear keys (from Park et al, 2004) detic Studies lu Viaducts, constructed as part of the Bolu Mountain Pass, is located in North-Central (Fig. 1).…”
Section: Geodetic Studiesmentioning
confidence: 99%
“…A post-earthquake investigation at the viaduct site revealed that the fault intersects the viaduct (between piers 44 and 45) at an angle of about 25 • , and the magnitude of the ground dislocation in the fault-parallel direction across the rupture was approximately 1.5 m. To understand the dynamic behaviour of the viaduct under earthquake conditions in the time history domain, a FEM modelling was implemented and the ground motion recorded at the Bolu station during the 1999 Düzce earthquake was used. The seismic performance of the Bolu viaducts was investigated by Park et al (2004) who studied the responses of passive control devices installed in the viaducts.…”
Section: Engineering Studiesmentioning
confidence: 99%
See 1 more Smart Citation